The effect of major adverse renal cardiovascular event (MARCE) incidence, procedure volume, and unit cost on the hospital savings resulting from contrast media use in inpatient angioplasty. (3rd April 2018) - Keuffel, Eric; McCullough, Peter A.; Todoran, Thomas M.; Brilakis, Emmanouil S.; Palli, Swetha R.; Ryan, Michael P.; Gunnarsson, Candace
Abstract: Objective: To determine the net economic impact of switching from low-osmolar contrast media (LOCM) to iso-osmolar contrast media (IOCM; iodixanol) in patients undergoing inpatient coronary or peripheral angioplasty in the United States (US). Methods: A budget impact model (BIM) was developed from a hospital perspective. Nationally representative procedural and contrast media prevalence rates, along with MARCE (major adverse renal cardiovascular event) incidence and episode-related cost data were derived from Premier Hospital Data (October 2014 to September 2015). A previously estimated relative risk reduction in MARCE associated with IOCM usage (9.3%) was applied. The higher cost of IOCM was included when calculating the net impact estimates at the aggregate, hospital type, and per hospital levels. One-way (±25%) and probabilistic sensitivity analyses identified the model's most important inputs. Results: Based on weighted analysis, 513, 882 US inpatient angioplasties and 35, 610 MARCE cases were estimated annually. Switching to an "IOCM only" strategy from a "LOCM only" strategy increases contrast media cost, but prevents 2, 900 MARCE events. The annual budget impact was an estimated saving of $30.71 million, aggregated across all US hospitals, $6, 316 per hospital, or $60 per procedure. Net savings were maintained across all univariate sensitivity analyses. While MARCE/event-free cost differential was the most important factor driving total net savings for hospitals in the Northeast and West, procedural volume was important in the Midwest and rural locations. Conclusions: Switching to an "IOCM only" strategy from a "LOCM only" approach yields substantial net global savings to hospitals, both at the national level and within hospital sub-groups. Hospital administrators should maintain awareness of the factors that are likely to be more influential for their hospital and recognize that purchasing on the basis of lower contrast media cost may result in higher overall costs for patients undergoing inpatient angioplasty.